Trending : how and why stuff gets popular - Vermond, Kira (Owlkids Books, 2020)
Investigates the social media phenomenon of "trending" and explores scientifically how and why certain ideas, fads, actions, behaviors, and items become trendy and popular. Examines how fads are sometimes crafted to lure people in and can actually become dangerous.